Perovskite cell, laminated cell and photovoltaic module
By introducing the polyvinylidene fluoride porous skeleton interface layer into the perovskite battery, the problem of single effect of passivation interface layer is solved, the photoelectric conversion efficiency and high temperature stability are improved, and the stability and efficiency of the perovskite battery are improved.
Patent Information
- Application Number
- CN202411580522.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-08-01
AI Technical Summary
The passivation interface layer effect of existing perovskite batteries is single, resulting in limited improvement in photoelectric conversion efficiency, and porous inorganic materials are prone to agglomeration, affecting the photogenerated carrier extraction efficiency and battery stability.
A first interface layer is provided between the perovskite layer and the hole transport layer, and/or a second interface layer is provided between the perovskite layer and the electron transport layer. The interface layer is composed of a polyvinylidene fluoride porous framework and an interface material, with a pore size and molecular weight within a specific range, and a pore transmission material is combined with an appropriate amount of hole transport material and perovskite material or electron transport material to form a porous insulating layer to inhibit interface non-radiative composite and material diffusion.
The photoelectric conversion efficiency and high temperature stability of perovskite batteries are significantly improved, and the stability of the battery structure is maintained by inhibiting the non-radiative composite of the interface and material diffusion.
Smart Images

Figure CN120417635A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cells, and particularly to a perovskite solar cell, a tandem solar cell, and a photovoltaic module. Background Art
[0002] Perovskite materials have excellent light absorption ability, and their light absorption ability can reach dozens of times that of crystalline silicon. Therefore, perovskite solar cells have high photoelectric conversion efficiency and are expected to become a new clean energy technology to replace traditional silicon-based solar cells.
[0003] In order to further improve the photoelectric conversion efficiency and stability of perovskite solar cells, it is currently often achieved through mechanisms such as surface passivation, crystal growth control, and energy band regulation. Among them, surface passivation is achieved by setting a passivation interface layer on the upper and lower surfaces of the perovskite layer. However, the current passivation interface layer mainly uses a single organic material or a porous inorganic material, and the passivation effect is relatively single. The improvement of the photoelectric conversion efficiency of perovskite solar cells is not high. Moreover, the commonly used porous inorganic materials (such as α-phase alumina) are prone to agglomeration and have poor distribution uniformity, which directly affects the photo-generated carrier extraction efficiency, recombination rate, and overall photoelectric stability of the battery. Summary of the Invention
[0004] The present invention provides a perovskite solar cell. By introducing a first interface layer and / or a second interface layer into the perovskite solar cell, the photoelectric conversion efficiency and high-temperature stability of the battery can be significantly improved.
[0005] The present invention also provides a tandem solar cell including the above perovskite solar cell, which has the advantages of high stability and high photoelectric conversion efficiency.
[0006] The present invention also provides a photovoltaic module including the above perovskite solar cell or tandem solar cell, which has the advantages of high photoelectric conversion efficiency and long service life.
[0007] Specifically, in a first aspect, the present invention provides a perovskite solar cell, which includes a hole transport layer, a perovskite layer, and an electron transport layer stacked in sequence; a first interface layer is provided between the perovskite layer and the hole transport layer, and / or a second interface layer is provided between the perovskite layer and the electron transport layer; wherein, the first interface layer and the second interface layer include: a polyvinylidene fluoride porous framework and an interface material filled in the polyvinylidene fluoride porous framework, and the molecular weight of the polyvinylidene fluoride porous framework is 50,000 g / mol - 1,000,000 g / mol.
[0008] Further, each of the first interface layer and the second interface layer independently includes a plurality of pores with a pore diameter of N, and N satisfies: 1 µm ≤ N ≤ 30 µm.
[0009] Furthermore, the first interface layer includes a number of pores with a pore size of 3 - 15 µm, and / or the second interface layer includes a number of pores with a pore size of 3 - 15 µm.
[0010] Furthermore, the molecular weight of the polyvinylidene fluoride porous framework is 200000 g / mol - 500000 g / mol.
[0011] Furthermore, the hole transport layer includes a hole transport material, the electron transport layer includes an electron transport material, and the interfacial material of the first interface layer includes a hole transport material and / or a perovskite material; and / or the interfacial material of the second interface layer includes an electron transport material and / or a perovskite material.
[0012] Furthermore, the perovskite material in the first interface layer is the same as the material of the perovskite layer, and / or the perovskite material in the second interface layer is the same as the material of the perovskite layer.
[0013] Furthermore, the interfacial material of the first interface layer includes a hole transport material and a perovskite material, and the molar ratio of the polyvinylidene fluoride porous framework, the perovskite material, and the hole transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1):(1×10 -2 -1);
[0014] and / or the interfacial material of the second interface layer includes an electron transport material and a perovskite material, and the molar ratio of the polyvinylidene fluoride porous framework, the perovskite material, and the electron transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1):(1×10 -2 -1).
[0015] Furthermore, the interfacial material of the first interface layer includes a hole transport material, and the molar ratio of the polyvinylidene fluoride porous framework and the hole transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1);
[0016] and / or the interfacial material of the second interface layer includes an electron transport material, and the molar ratio of the polyvinylidene fluoride porous framework and the electron transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1).
[0017] The interfacial material of the first interfacial layer includes a hole transport material and a perovskite material; the interfacial material of the second interfacial layer includes an electron transport material, wherein, in the first interfacial layer, the molar ratio of the polyvinylidene fluoride porous framework, the perovskite material and the hole transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1):(1×10 -2 -1);
[0018] And / or, in the second interfacial layer, the molar ratio of the polyvinylidene fluoride porous framework and the electron transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1).
[0019] Furthermore, the hole transport material is one or more of amine halide, formamidinium hydrohalide, methylammonium hydrohalide, inorganic metal halide, octylamine halide, phenethylamine halide, polycarbazole phosphate, [6,6]-phenyl-C61-butyric acid methyl ester, inorganic metal oxide;
[0020] And / or, the electron transport material is one or more of titanium nitride, tin oxide, titanium oxide, nickel oxide, fullerene, fullerene derivative.
[0021] Furthermore, the perovskite battery further includes a transparent conductive substrate, and the transparent conductive substrate is located on the surface of the hole transport layer away from the perovskite layer.
[0022] Furthermore, the perovskite battery includes: a transparent conductive substrate, a hole transport layer, the first interfacial layer, a perovskite layer, the second interfacial layer, an electron transport layer and an electrode which are stacked in sequence.
[0023] Furthermore, a hole blocking layer is provided on the surface of the electron transport layer.
[0024] Furthermore, the thickness of the first interfacial layer is 0.1-50 nm; and / or, the thickness of the second interfacial layer is 0.1-50 nm.
[0025] Furthermore, the thickness of the first interfacial layer is 1-15 nm; and / or, the thickness of the second interfacial layer is 1-15 nm.
[0026] Second, the present invention provides a preparation method of a perovskite battery, including the following steps:
[0027] The first interfacial material is dispersed in a solvent, polyvinylidene fluoride is added, and the concentration of polyvinylidene fluoride is 1-200 mg / mL, and the concentration of the first interfacial material is 0.1-200 mg / mL. After mixing, a first slurry is obtained, and the first slurry is coated on the surface of the hole transport layer to obtain a first interfacial layer;
[0028] A perovskite precursor solution is coated on the surface of the first interfacial layer, and a perovskite layer is obtained after annealing;
[0029] The second interfacial material is dispersed in a solvent, polyvinylidene fluoride is added, and the concentration of polyvinylidene fluoride is 1-200 mg / mL, and the concentration of the second interfacial material is 0.1-200 mg / mL. After mixing, a second slurry is obtained, and the second slurry is coated on the surface of the perovskite layer to obtain a second interfacial layer;
[0030] An electron transport layer is fabricated on the surface of the second interfacial layer.
[0031] Furthermore, in the first slurry, the concentration of polyvinylidene fluoride is 10-50 mg / mL, and the concentration of the first interfacial material is 0.3-100 mg / mL;
[0032] And / or, in the second slurry, the concentration of polyvinylidene fluoride is 0.5-5 mg / mL, and the concentration of the second interfacial material is 0.3-100 mg / mL.
[0033] Hole transport layer, hole transport layer, electron transport layer. Thirdly, the present invention provides a tandem cell, comprising the perovskite cell described in the first aspect.
[0034] Fourthly, the present invention provides a photovoltaic module, comprising the perovskite cell described in the first aspect or the tandem cell described in the third aspect.
[0035] For the perovskite cell provided by the present invention, by providing a first interfacial layer between the perovskite layer and the hole transport layer, and / or providing a second interfacial layer between the perovskite layer and the electron transport layer, the stability and photoelectric conversion efficiency of the perovskite cell can be significantly improved. Description of the Drawings
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the related art, the following briefly introduces the drawings required to be used in the description of the embodiments of the present invention or the related art. Obviously, the following drawings are only some embodiments of the present invention, and those of ordinary skill in the art can also obtain other drawings based on these drawings without creative efforts.
[0037] Figure 1 SEM image of the first interfacial layer of the perovskite cell in Example 1;
[0038] Figure 2 EDS diagram of the first interface layer of the perovskite solar cell of Example 1;
[0039] Figure 3 XPS diagrams of sample FTO / NiOx before and after aging in Test Example 1;
[0040] Figure 4 XPS diagrams of sample FTO / NiOx / perovskite layer before and after aging in Test Example 1;
[0041] Figure 5 XPS diagrams of sample FTO / NiOx / PVDF / perovskite layer before and after aging in Test Example 1. Detailed implementation manners
[0042] To enable those skilled in the art to better understand the solution of the present invention, the present invention will be further described in detail below. The specific implementation manners listed below only describe the principles and features of the present invention, and the examples given are only used to explain the present invention, not to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation manners obtained by those of ordinary skill in the art without creative efforts fall within the scope of protection of the present invention.
[0043] In the present application, the terms "first" and "second" are only used for descriptive purposes to distinguish objects such as substances from each other, and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity of the indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined with "first" and "second" may explicitly or implicitly include one or more of such features.
[0044] In the present application, the reference to "an implementation manner", "an embodiment", "an example" or "an example" means that the specific features, structures or characteristics described in connection with the implementation manner, embodiment or example are included in at least one embodiment of the present invention. Therefore, the phrases "an implementation manner", "an embodiment", "an embodiment", "an example" or "an example" that appear in various places throughout the specification do not necessarily refer to the same embodiment or example. In addition, the specific features, structures or characteristics may be combined in one or more embodiments or examples in any appropriate combination and / or sub-combination.
[0045] In the prior art, an organic material or a porous insulating inorganic material is often used to form a passivation interface layer to further improve the photoelectric conversion efficiency and stability of perovskite solar cells. However, the passivation effect of the current passivation interface layer is relatively single, the improvement of the photoelectric conversion efficiency of perovskite solar cells is limited, and it is difficult to ensure its stability. Therefore, the present invention adopts the following technical solutions:
[0046] In a first aspect, the present invention provides a perovskite solar cell, comprising a hole transport layer, a perovskite layer, and an electron transport layer stacked in sequence; a first interface layer is provided between the perovskite layer and the hole transport layer, and / or a second interface layer is provided between the perovskite layer and the electron transport layer; wherein, the first interface layer and the second interface layer comprise: a polyvinylidene fluoride porous framework and an interface material filled in the polyvinylidene fluoride porous framework, and the molecular weight of the polyvinylidene fluoride porous framework is 50,000 g / mol - 1,000,000 g / mol.
[0047] It should be noted that the perovskite solar cell of the present invention can be provided with both a first interface layer and a second interface layer, or only a first interface layer or a second interface layer. In either case, the photoelectric conversion efficiency of the perovskite solar cell can be effectively improved, and its high-temperature stability can be ensured. In addition, both the first interface layer and the second interface layer comprise a polyvinylidene fluoride porous framework and an interface material filled in the polyvinylidene fluoride porous framework. However, their specific compositions, such as: the molecular weight of the polyvinylidene fluoride porous framework and its proportion in the first / second interface layer, the composition of the interface material and its proportion in the first / second interface layer, can be the same or different, and the present invention does not make a special limitation on this.
[0048] In the present invention, by providing a first interface layer between the perovskite layer and the hole transport layer, and / or a second interface layer between the perovskite layer and the electron transport layer, the stability and photoelectric conversion efficiency of the perovskite solar cell can be significantly improved. Specifically: Firstly, in the present invention, a porous insulating layer is formed between the charge transport layer and the perovskite layer by using a polyvinylidene fluoride porous framework, which can effectively inhibit the interfacial non-radiative recombination between the perovskite and the charge transport layer, reduce the direct contact area between the functional layers, and thus improve the photoelectric conversion efficiency of the perovskite solar cell. Secondly, the polyvinylidene fluoride porous framework can also effectively slow down the mutual diffusion of materials between the perovskite layer and the charge transport layer and maintain the stability of the battery structure. Thirdly, the polyvinylidene fluoride porous framework and the interfacial material filled in the polyvinylidene fluoride porous framework can maintain a stable structure under the battery working environment and play a good connecting role between the upper and lower charge transport layers. Fourthly, the fluorine atoms in the polyvinylidene fluoride can form strong interactions with the metal ions in the perovskite layer to passivate defects, thereby effectively reducing non-radiative losses. In addition, the polyvinylidene fluoride porous framework with the above specific molecular weight can reduce non-radiative recombination losses and ensure the uniformity of the first interface layer and the second interface layer. If the molecular weight of the polyvinylidene fluoride porous framework is less than 50,000 g / mol, the strong hydrogen bonds formed between the polyvinylidene fluoride and the organic cations in the perovskite layer and the charge transport layer will be reduced, increasing non-radiative recombination losses. If the molecular weight of the polyvinylidene fluoride porous framework is greater than 1,000,000 g / mol, the polyvinylidene fluoride is difficult to disperse and prone to agglomeration, affecting the uniformity of the first interface layer and the second interface layer.
[0049] In an alternative embodiment, the first interface layer and the second interface layer include a plurality of pores with a pore size of N, where N satisfies: 1 µm ≤ N ≤ 30 µm.
[0050] When the pore size of the first interface layer or the second interface layer is within the above range, it can further ensure the inhibitory effect of the first interface layer and the second interface layer on the mutual diffusion between the perovskite layer and the charge transport layer, while avoiding the polyvinylidene fluoride from hindering the movement of carriers between the perovskite layer and the charge transport layer, thereby maintaining the stability of the battery structure and the photoelectric conversion efficiency.
[0051] By providing a first interface layer between the perovskite layer and the hole transport layer and a second interface layer between the perovskite layer and the electron transport layer, this embodiment can make the perovskite layer, the first interface layer and the second interface layer form a sandwich-like structure, which can further improve the stability and photoelectric conversion efficiency of the perovskite solar cell.
[0052] In an alternative embodiment, the first interface layer includes a plurality of pores with a pore size of 3 - 15 µm, and the second interface layer includes a plurality of pores with a pore size of 3 - 15 µm. Among them, when the pore size of the first interface layer or the second interface layer is within the range of 3 - 15 µm, it can further ensure the stability of the battery structure.
[0053] It can be understood that the pore size distributions of the above-mentioned first interface layer and the second interface layer are independent of each other, and the pore sizes of a number of pores included in both are the same, different, or partially the same.
[0054] In an optional embodiment, the molecular weight of the polyvinylidene fluoride porous framework is 200,000 g / mol - 500,000 g / mol. The polyvinylidene fluoride porous framework within the above range is more conducive to reducing the non-radiative recombination loss of the perovskite solar cell, and at the same time makes the surfaces of the first interface layer and the second interface layer more uniform, which can further ensure the stability of the cell structure.
[0055] Exemplarily, the molecular weight of the above-mentioned polyvinylidene fluoride porous framework is any value among 200,000 g / mol, 250,000 g / mol, 300,000 g / mol, 350,000 g / mol, 400,000 g / mol, 450,000 g / mol, etc., or a range composed of any two of them.
[0056] In an optional embodiment, the hole transport layer includes a hole transport material, the electron transport layer includes an electron transport material, the interface material of the first interface layer includes a first charge transport material and / or a perovskite material; the interface material of the second interface layer includes a second charge transport material and / or a perovskite material.
[0057] When the interface material of the first interface layer includes a hole transport material and / or a perovskite material, it can further passivate the interface defects between the perovskite layer and the hole transport layer, match the energy levels of the functional layers, and promote carrier transport / extraction. Moreover, the fluorine atoms in the polyvinylidene fluoride can form strong hydrogen bonds with the organic cations of the first charge transport material, further passivating the interface defects, thereby reducing the interface non-radiative loss. When the interface material of the second interface layer includes an electron transport material and / or a perovskite material, it can further passivate the interface defects between the perovskite layer and the electron transport layer, promote carrier transport / extraction, and the fluorine atoms in the polyvinylidene fluoride can form strong hydrogen bonds with the organic cations of the electron transport material, further passivating the interface defects, thereby reducing the interface non-radiative loss. Further, when the interface material of the first interface layer and / or the second interface layer includes a perovskite material, due to the excellent crystallinity and fewer defect states of the perovskite material itself, using it for interface passivation can effectively reduce interface defects and reduce the rate of non-radiative recombination.
[0058] In an optional embodiment, the perovskite material in the first interface layer is the same as the material of the perovskite layer, and / or the perovskite material in the second interface layer is the same as the material of the perovskite layer.
[0059] In an alternative embodiment, when the perovskite cell includes the first interface layer and the second interface layer, the perovskite materials in the first interface layer, the material of the perovskite layer, and the perovskite materials in the second interface layer are the same.
[0060] The above embodiments can be optimized by adjusting the chemical composition of the perovskite material to better match the energy levels between the interface layer and the perovskite layer, which helps to further reduce the energy loss at the interface and improve the carrier transport efficiency.
[0061] In an alternative embodiment, the interface material of the first interface layer includes a hole transport material and a perovskite material, and the molar ratio of the polyvinylidene fluoride porous framework, the perovskite material, and the hole transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1):(1×10 -2 -1);
[0062] And / or, the interface material of the second interface layer includes an electron transport material and a perovskite material, and the molar ratio of the polyvinylidene fluoride porous framework, the perovskite material, and the electron transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1):(1×10 -2 -1).
[0063] In an alternative embodiment, the interface material of the first interface layer includes a hole transport material, and the molar ratio of the polyvinylidene fluoride porous framework and the hole transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1);
[0064] And / or, the interface material of the second interface layer includes an electron transport material, and the molar ratio of the polyvinylidene fluoride porous framework and the electron transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1).
[0065] Among them, the polyvinylidene fluoride porous framework of the above embodiments and the interface material with an appropriate ratio can balance the structural stability of the battery and the interlayer movement rate of carriers between the perovskite layer and the first interface layer or the second interface layer, thereby enhancing the overall light absorption of the battery, and thus improving the photoelectric conversion efficiency and high-temperature stability.
[0066] In an optional embodiment, the hole transport material is one or more of amine halide, formamidinium hydrohalide, methylammonium hydrohalide, inorganic metal halide, octylamine halide, phenethylamine halide, polycarbazole phosphate, [6,6]-phenyl-C61-butyric acid methyl ester, inorganic metal oxide; and / or,
[0067] The electron transport material is one or more of titanium nitride, tin oxide, titanium oxide, nickel oxide, fullerene, fullerene derivatives.
[0068] In an optional embodiment, the perovskite cell further includes a transparent conductive substrate, and the transparent conductive substrate is located on the surface of the hole transport layer away from the perovskite layer.
[0069] It can be understood that in the present invention, the perovskite cell can be a reverse (p-i-n) structure or a normal (n-i-p) structure.
[0070] When the perovskite cell is of a reverse (p-i-n) structure, in an optional embodiment, the perovskite cell includes: a transparent conductive substrate, a hole transport layer, the first interface layer, a perovskite layer, the second interface layer, an electron transport layer, and an electrode, which are stacked in sequence.
[0071] When the perovskite cell is of a normal (n-i-p) structure, in an optional embodiment, the perovskite cell includes: a transparent conductive substrate, an electron transport layer, the first interface layer, a perovskite layer, the second interface layer, a hole transport layer, and an electrode, which are stacked in sequence.
[0072] In an optional embodiment, a hole blocking layer is provided on the surface of the electron transport layer.
[0073] In a specific embodiment, the surface of the electron transport layer is covered with a BCP passivation layer. Among them, the passivation layer can reduce surface defects and interface states, thereby avoiding carrier recombination and reducing the efficiency of the device.
[0074] In a specific embodiment, the material of the BCP passivation layer is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, also known as bathocuproine, and its energy band can guide electrons to pass through while holes cannot pass through. Therefore, a BCP passivation layer is formed on the surface of the electron transport layer to block the diffusion of holes to the electrode and prevent metal ions in the electrode from damaging the transport layer.
[0075] The perovskite layer is the core part of the perovskite solar cell, responsible for absorbing light and generating photo-generated carriers (electrons and holes). In some embodiments of the present invention, the above-mentioned perovskite layer composition is A x A' (1-x)BX3, where A is one or more of FA and MA, A' is one or more of Cs, Ka, Na, Ca, and Rb, B is one or more of Pb and Sn, and X is one or more of I, Br, and Cl. Preferably, A:A':B:X = (0.5 - 0.99):(0.01 - 0.50):1:3.
[0076] The selection of the thickness of the perovskite layer has a certain impact on the photoelectric conversion efficiency, charge transport performance, and stability of the battery. Those skilled in the art can prepare a perovskite layer with an appropriate thickness according to different materials and preparation processes. In some embodiments of the present invention, the thickness of the perovskite layer is 100 nm - 1000 nm. Within this range, as the thickness of the perovskite layer increases, the battery can absorb more photons and generate more photo-generated carriers, thereby improving the photoelectric conversion efficiency. Exemplarily, the thickness of the perovskite layer can be 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 700 nm, 800 nm, 900 nm, etc.
[0077] In a specific embodiment, the material of the electron transport layer is one or more of titanium nitride, tin oxide, titanium oxide, nickel oxide, fullerene (C60), and fullerene derivatives; Exemplarily, the fullerene derivative is [6,6]-phenyl-C61-butyric acid methyl ester (PCBM).
[0078] In some embodiments of the present invention, the thickness of the electron transport layer is 20 - 200 nm. Among them, when the thickness of the electron transport layer is controlled within the above range, the perovskite solar cell has a relatively high photoelectric conversion efficiency. This is because within this thickness range, the electron transport layer can not only effectively collect and transport electrons but also maintain good light absorption ability. Exemplarily, the thickness of the electron transport layer can be 20 nm, 22 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 58 nm, 60 nm, etc.
[0079] In a specific embodiment, the material of the hole transport layer includes one or more of amine halides, formamidinium hydrogen halides, methylammonium hydrogen halides, inorganic metal halides, octylamine halides, phenethylamine halides, polycarbazole phosphoric acid, and inorganic metal oxides; Exemplarily, the material of the hole transport layer is specifically one or more of 2,2',7,7'-tetrakis[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-MeOTAD), polybis(4-phenyl)(2,4,6-trimethylphenyl)amine (PTAA), poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS), CuOx, and NiOx.
[0080] In some embodiments of the present invention, the thickness of the hole transport layer is in the range of 15 nm - 30 nm. Among them, a hole transport layer with an appropriate thickness can not only completely cover the conductive substrate, but also ensure the smooth collection of carriers, avoiding the phenomenon that excessive absorption of photons leads to a decrease in the short-circuit current density of the battery. Exemplarily, the thickness of the hole transport layer can be 15 nm, 18 nm, 20 nm, 25 nm, 28 nm, 30 nm, etc.
[0081] In some embodiments of the present invention, the material of the electrode is one or more of metal materials: aluminum, copper, silver, gold, or carbon materials. The carbon materials can be selected from one or more of Ketjen black, acetylene black, carbon nanotubes, and graphene.
[0082] In some embodiments of the present invention, when the material of the electrode is selected from carbon materials, a binder is further included. The binder can be selected from one or more of acrylic resin, polyvinylidene fluoride, polyvinyl acetate, ethylene-vinyl acetate copolymer, polymethyl methacrylate, polycarbonate, polyamide, and polystyrene.
[0083] In some embodiments of the present invention, the transparent conductive substrate is a flexible polymer material or a metal film covered with a transparent electrode, and the area is 0.05 to 20000 cm 2 . Exemplarily, the materials of the transparent electrode include indium tin oxide (ITO), fluorine-doped tin oxide (FTO), carbon nanotubes, graphene. The polymer materials include polyethylene naphthalate, polyethylene terephthalate, and the materials of the metal film include aluminum, copper, and silver.
[0084] First interface layer and second interface layer with appropriate thicknesses can effectively cover interface defects, reduce non-radiative recombination, and improve the carrier lifetime and the open-circuit voltage of the device. If the first interface layer and / or the second interface layer are too thin, they may not be able to fully cover the interface defects, reducing the passivation effect. However, if the passivation layer is too thick, it may increase the length of the charge transport path, resulting in an increase in resistance and thus reducing the charge transport efficiency. Therefore, in an optional embodiment, the thickness of the first interface layer is 0.1 - 50 nm; and / or, the thickness of the second interface layer is 0.1 - 50 nm.
[0085] In an optional embodiment, the thickness of the first interface layer is 1 - 15 nm; and / or, the thickness of the second interface layer is 1 - 15 nm. Among them, the first interface layer and / or the second interface layer with the above-mentioned thicknesses are more conducive to the effective transport of electrons and holes, reducing charge recombination, and thus can further ensure the photoelectric conversion efficiency of the battery.
[0086] In a second aspect, the present invention provides a method for preparing a perovskite battery pack, comprising the following steps:
[0087] Disperse the first interfacial material in a solvent, add polyvinylidene fluoride, and make the concentration of polyvinylidene fluoride be 1 - 200 mg / mL, and the concentration of the first interfacial material be 0.1 - 200 mg / mL. After mixing, obtain the first slurry, and coat the first slurry on the surface of the hole transport layer to obtain the first interfacial layer;
[0088] Coat the perovskite precursor solution on the surface of the first interfacial layer, and obtain the perovskite layer after annealing;
[0089] Disperse the second interfacial material in a solvent, add polyvinylidene fluoride, and make the concentration of polyvinylidene fluoride be 1 - 200 mg / mL, and the concentration of the second interfacial material be 0.1 - 200 mg / mL. After mixing, obtain the second slurry, and coat the second slurry on the surface of the perovskite layer to obtain the second interfacial layer;
[0090] In an optional embodiment, in the first slurry, the concentration of polyvinylidene fluoride is 10 - 50 mg / mL, and the concentration of the interfacial material is 0.3 - 100 mg / mL; in the second slurry, the concentration of polyvinylidene fluoride is 0.5 - 5 mg / mL, and the concentration of the interfacial material is 0.3 - 100 mg / mL.
[0091] Exemplarily, the above preparation method specifically includes the following process:
[0092] 1) The transparent conductive substrate is ultrasonically cleaned with dishwashing detergent water, deionized water, ethanol, and isopropanol for 10 minutes in sequence, then dried with a nitrogen air gun, and subjected to ozone or plasma treatment for 5 - 20 min;
[0093] 2) Deposit the hole transport layer on the treated transparent conductive substrate, and perform the next operation after deposition.
[0094] 3) Disperse the first interfacial material in an organic solvent, add polyvinylidene fluoride, and after mixing evenly, obtain the first slurry, and deposit the first slurry on the hole transport layer to obtain the first interfacial layer;
[0095] 4) Deposit the perovskite precursor solution on the first interfacial layer, and perform anti-solvent or vacuum pumping treatment, and then perform annealing treatment, or heat in vacuum for vacuum annealing treatment;
[0096] 5) Disperse the second interfacial material in an organic solvent, and after mixing evenly, obtain the second slurry, and deposit the second slurry on the perovskite layer to obtain the second interfacial layer, and perform the next operation after deposition;
[0097] 6) Deposit the electron transport layer on the second interfacial layer.
[0098] 7) Deposit the electrode by magnetron sputtering, thermal evaporation, electron beam evaporation, screen printing, coating, slot coating or spraying.
[0099] In the above preparation method, when the electron transport layer is titanium nitride, the deposition method of the titanium nitride is magnetron sputtering, thermal evaporation, electron beam evaporation, screen printing, coating, slot coating or spraying.
[0100] The organic solvent in step 3) is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, γ-hydroxybutyrolactone, isopropanol, diphenyl sulfoxide, ethyl acetate;
[0101] The solvent of the perovskite precursor solution in step 4) is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, γ-hydroxybutyrolactone, isopropanol, diphenyl sulfoxide, ethyl acetate, and the anti-solvent is one or more of chlorobenzene, acetonitrile, ethanol, isopropanol, ethyl acetate, diethyl ether. The vacuum degree of the vacuum treatment is 50 - 5000 Pa, the time is 10 s - 1000 s, the annealing temperature is 50 - 200 °C, and the time is 5 - 500 min.
[0102] In the third aspect, the present invention provides a perovskite battery pack, comprising the perovskite battery described in the first aspect.
[0103] In the fourth aspect, the present invention provides a photovoltaic module, comprising the perovskite battery described in the first aspect or the perovskite battery pack described in the third aspect.
[0104] The technical solution of the present invention is further described below in conjunction with specific embodiments. All parts, percentage contents and ratios recorded in the following embodiments are based on weight. Moreover, all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments used in the embodiments are all commercially available.
[0105] Example 1
[0106] This example provides a p-i-n structure perovskite battery, including a glass substrate with a thickness of 5 mm (covered with FTO with a thickness of 400 nm), a hole transport layer (NiOx) with a thickness of 20 nm, a first interface layer with a thickness of 5 nm, a perovskite layer with a thickness of 600 nm (FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 ), a second interface layer with a thickness of 5 nm, an electron transport layer (fullerene) with a thickness of 30 nm, a 7 nm BCP passivation layer and a silver electrode with a thickness of 100 nm;
[0107] Among them, the first interface layer includes a polyvinylidene fluoride porous framework and perovskite FA filled in the polyvinylidene fluoride porous framework 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 and polycarbazole phosphate; the molecular weight of the polyvinylidene fluoride porous framework is 200,000 g / mol; the second interface layer includes a polyvinylidene fluoride porous framework and PCBM filled in the polyvinylidene fluoride porous framework; the molecular weight of the polyvinylidene fluoride porous framework is 200,000 g / mol;
[0108] In the first interface layer, there are several pores with a pore diameter of 6-8 µm, and the molar ratio of the polyvinylidene fluoride porous framework, FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 and polycarbazole phosphate is 1×10 -4 : 1×10 -1 : 1×10 -1 ;
[0109] In the second interface layer, there are several pores with a pore diameter of 6-8 µm, and the molar ratio of the polyvinylidene fluoride porous framework and PCBM is 1×10 -4 :1×10 -1 .
[0110] Its preparation method includes the following steps:
[0111] 1) Dissolve 0.1 g of polyvinylidene fluoride (PVDF molecular weight: 200,000 g / mol) in 1 mL of N-methylpyrrolidone; mix 1 mg of polycarbazole phosphate thoroughly in 1 mL of the perovskite precursor solution, and this precursor solution is 50 mg / mL of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , and the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide. Mix the polyvinylidene fluoride solution and the precursor solution in a volume ratio of 3:7 to complete the solution preparation of the first interface layer;
[0112] 2) Dissolve 0.3 g of polyvinylidene fluoride (molecular weight: 200,000 g / mol) in 1 mL of N-methylpyrrolidone; mix 5 mg of PCBM in 1 mL of toluene solution; mix the polyvinylidene fluoride solution and the PCBM solution in a volume ratio of 1:9 to complete the solution preparation of the second interface layer;
[0113] 3) Deposit a hole transport layer NiOx, a first interface layer, and FA of 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 on a glass substrate in sequence, then deposit a second interface layer, an electron transport layer C60, and a blocking layer BCP, and finally evaporate a 100-nm silver electrode to complete the preparation of the battery.
[0114] After depositing the first interface layer on the glass substrate in sequence, use a scanning electron microscope (SEM) to test and observe its surface. The results are shown in Figure 1 Subsequently, use an energy-dispersive spectrometer (EDS) to observe the distribution of F element on its surface. The results are shown in Figure 2 It can be seen therefrom that the surface of the first interface layer in this example is flat and the distribution of F element is uniform, indicating that the polyvinylidene fluoride porous framework is relatively uniformly dispersed in the interface layer.
[0115] Example 2
[0116] The difference between the perovskite battery in this example and that in Example 1 is that the molecular weight of the polyvinylidene fluoride porous framework in the first interface layer and the second interface layer is 500000 g / mol, and the thickness of both the first interface layer and the second interface layer is 7 nm, and the others are the same as those in Example 1.
[0117] [[ID=2⑧]]Example 3
[0118] The difference between the perovskite battery in this example and that in Example 1 is that the molecular weight of the polyvinylidene fluoride porous framework in the first interface layer and the second interface layer is 100000 g / mol, and the thickness of both the first interface layer and the second interface layer is 4 nm, and the others are the same as those in Example 1.
[0119] Example 4
[0120] The difference between the perovskite battery in this example and that in Example 1 is that the concentration of the used polyvinylidene fluoride is reduced so that the thickness of both the first interface layer and the second interface layer is 3 nm, and the pore sizes of both are in the range of 12 - 15 µm;
[0121] The difference in its preparation method from that in Example 1 is that:
[0122] 1) Dissolve 0.05 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) in 1 mL of N-methylpyrrolidone; mix 1 mg of polycarbazole phosphate thoroughly in 1 mL of the perovskite precursor solution, and this precursor solution is 50 mg / mL of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br0.3 , the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide. The polyvinylidene fluoride solution and the precursor solution are fully mixed at a volume ratio of 3:7 to complete the preparation of the solution for the first interfacial layer;
[0123] 2) Dissolve 0.1 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) in 1 mL of N-methylpyrrolidone; mix 5 mg of PCBM in 1 mL of toluene solution; fully mix the polyvinylidene fluoride solution and the PCBM solution at a volume ratio of 1:9 to complete the preparation of the solution for the second interfacial layer.
[0124] Example 5
[0125] The difference between the perovskite solar cell and Example 1 is that the concentration of polyvinylidene fluoride used is increased, such that the thicknesses of both the first interfacial layer and the second interfacial layer are 10 nm, and the pore sizes of both are in the range of 3 - 5 µm.
[0126] The difference in its preparation method from Example 1 is that:
[0127] 1) Dissolve 0.3 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) in 1 mL of N-methylpyrrolidone; fully mix 1 mg of polycarbazole phosphate in 1 mL of the perovskite precursor solution, and this precursor solution is 50 mg / mL of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide. The polyvinylidene fluoride solution and the precursor solution are fully mixed at a volume ratio of 3:7 to complete the preparation of the solution for the first interfacial layer;
[0128] 2) Dissolve 0.5 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) in 1 mL of N-methylpyrrolidone; mix 5 mg of PCBM in 1 mL of toluene solution; fully mix the polyvinylidene fluoride solution and the PCBM solution at a volume ratio of 1:9 to complete the preparation of the solution for the second interfacial layer.
[0129] Example 6
[0130] The difference between the perovskite solar cell and Example 1 is that it does not include the second interfacial layer, and the others are the same as Example 1.
[0131] Example 7
[0132] The difference between the perovskite solar cell and Example 1 is that it does not include the first interfacial layer, and the others are the same as Example 1.
[0133] Example 8
[0134] The difference between the perovskite solar cell and Example 1 is that in the first interfacial layer, the molar ratio of polyvinylidene fluoride porous framework, FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 and polycarbazole phosphate is 1×10 -3 :1:1;
[0135] In the second interfacial layer, the molar ratio of polyvinylidene fluoride porous framework and PCBM is 1×10 -3 :1.
[0136] Its preparation method includes the following steps:
[0137] 1) Dissolve 1 g of polyvinylidene fluoride (PVDF, molecular weight: 200000 g / mol) in 1 mL of N-methylpyrrolidone; mix 10 mg of polycarbazole phosphate thoroughly in 1 mL of the perovskite precursor solution, which is 500 mg / mL of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , and the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide. Mix the polyvinylidene fluoride solution and the precursor solution in a volume ratio of 3:7 to complete the solution preparation of the first interfacial layer;
[0138] 2) Dissolve 3 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) in 1 mL of N-methylpyrrolidone; mix 50 mg of PCBM in 1 mL of toluene solution; mix the polyvinylidene fluoride solution and the PCBM solution in a volume ratio of 1:9 to complete the solution preparation of the second interfacial layer;
[0139] Example 9
[0140] The difference between the perovskite solar cell and Example 1 is that in the first interfacial layer, the molar ratio of polyvinylidene fluoride porous framework, FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 and polycarbazole phosphate is 1×10 -5 :1×10 -2 :1×10 -2 ;
[0141] In the second interfacial layer, the molar ratio of polyvinylidene fluoride porous framework and PCBM is 1×10 -5 :1×10-2 。
[0142] Its preparation method comprises the following steps:
[0143] 1) Dissolve 0.01 g of polyvinylidene fluoride (PVDF, molecular weight: 200000 g / mol) thoroughly in 1 mL of N-methylpyrrolidone; mix 0.01 mg of polycarbazole phosphate thoroughly in 1 mL of the perovskite precursor solution, and this precursor solution is 5 mg / mL of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , and the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide. Mix the polyvinylidene fluoride solution and the precursor solution thoroughly at a volume ratio of 3:7 to complete the preparation of the solution for the first interfacial layer;
[0144] 2) Dissolve 0.03 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) thoroughly in 1 mL of N-methylpyrrolidone; mix 0.5 mg of PCBM in 1 mL of toluene solution; mix the polyvinylidene fluoride solution and the PCBM solution thoroughly at a volume ratio of 1:9 to complete the preparation of the solution for the second interfacial layer;
[0145] Example 10
[0146] The difference between the perovskite cell and Example 1 is that the first interfacial layer comprises a polyvinylidene fluoride porous framework and PCBM filled in the polyvinylidene fluoride porous framework;
[0147] In the second interfacial layer, the molar ratio of the polyvinylidene fluoride porous framework to PCBM is 1×10 -5 :1×10 -2 。
[0148] Its preparation method comprises the following steps:
[0149] 1) Dissolve 0.03 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) thoroughly in 1 mL of N-methylpyrrolidone; mix 0.5 mg of PCBM in 1 mL of toluene solution; mix the polyvinylidene fluoride solution and the PCBM solution thoroughly at a volume ratio of 1:9 to complete the preparation of the solution for the second interfacial layer;
[0150] Example 11
[0151] The difference between the perovskite cell and Example 1 is that the first interfacial layer comprises a polyvinylidene fluoride porous framework and PCBM filled in the polyvinylidene fluoride porous framework;
[0152] In the second interfacial layer, the molar ratio of polyvinylidene fluoride porous skeleton to PCBM is 1×10 -3 :1.
[0153] Its preparation method includes the following steps:
[0154] 1) Dissolve 3 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) thoroughly in 1 mL of N-methylpyrrolidone; mix 50 mg of PCBM in 1 mL of toluene solution; mix the polyvinylidene fluoride solution and the PCBM solution thoroughly at a volume ratio of 1:9 to complete the preparation of the solution for the second interfacial layer;
[0155] Example 12
[0156] The difference between the perovskite solar cell and Example 1 is that: by reducing the concentration of polyvinylidene fluoride used, the thicknesses of both the first interfacial layer and the second interfacial layer are 12 - 15 nm, and the pore sizes of both are in the range of 1 - 5 µm.
[0157] Its preparation method includes the following steps:
[0158] 1) Dissolve 1 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) thoroughly in 1 mL of N-methylpyrrolidone; mix 1 mg of polycarbazole phosphate thoroughly in 1 mL of the perovskite precursor solution, and this precursor solution is 50 mg / mL of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , and the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide. Mix the polyvinylidene fluoride solution and the precursor solution thoroughly at a volume ratio of 3:7 to complete the preparation of the solution for the first interfacial layer;
[0159] 2) Dissolve 3 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) thoroughly in 1 mL of N-methylpyrrolidone; mix 5 mg of PCBM in 1 mL of toluene solution; mix the polyvinylidene fluoride solution and the PCBM solution thoroughly at a volume ratio of 1:9 to complete the preparation of the solution for the second interfacial layer.
[0160] Example 13
[0161] The difference between the perovskite solar cell and Example 1 is that: by reducing the concentration of polyvinylidene fluoride used, the thicknesses of the first interfacial layer and the second interfacial layer are 1 - 2 nm, and the pore sizes of both are in the range of 25 - 30 µm.
[0162] Its preparation method includes the following steps:
[0163] 1) Dissolve 0.01 g of polyvinylidene fluoride (molecular weight: 200,000 g / mol) thoroughly in 1 mL of N-methylpyrrolidone; mix 1 mg of polycarbazole phosphate thoroughly in 1 mL of the perovskite precursor solution, which is a 50 mg / mL solution of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , and the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide. Mix the polyvinylidene fluoride solution and the precursor solution thoroughly at a volume ratio of 3:7 to complete the preparation of the solution for the first interfacial layer;
[0164] 2) Dissolve 0.03 g of polyvinylidene fluoride (molecular weight: 200,000 g / mol) thoroughly in 1 mL of N-methylpyrrolidone; mix 5 mg of PCBM in 1 mL of toluene solution; mix the polyvinylidene fluoride solution and the PCBM solution thoroughly at a volume ratio of 1:9 to complete the preparation of the solution for the second interfacial layer.
[0165] Comparative Example 1
[0166] The difference between the perovskite solar cell and Example 1 is that: there is no polyvinylidene fluoride in the first interfacial layer and the second interfacial layer; and the first interfacial layer and the second interfacial layer include pores with a pore size less than 1 µm.
[0167] The difference in its preparation method from Example 1 is that:
[0168] 1) Mix 1 mg of polycarbazole phosphate thoroughly in 1 mL of the perovskite precursor solution, which is a 50 mg / mL solution of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , and the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide (volume ratio is 4:1) to complete the preparation of the solution for the first interfacial layer;
[0169] 2) Mix 5 mg of PCBM in 1 mL of toluene solution to complete the preparation of the solution for the second interfacial layer.
[0170] Comparative Example 2
[0171] The difference between the perovskite solar cell and Example 1 is that: there is no first interfacial layer and second interfacial layer, but 2 mg / mL of polyvinylidene fluoride (molecular weight: 200,000 g / mol) is added to the perovskite layer.
[0172] Comparative Example 3
[0173] The difference between the perovskite solar cell and Example 1 is that the first interface layer and the second interface layer only contain polyvinylidene fluoride, and the pore size is 6 - 8 nm.
[0174] Comparative Example 4
[0175] The difference between the perovskite solar cell and Example 1 is that the thickness of the first interface layer and the second interface layer is 7 nm, and the molecular weight of polyvinylidene fluoride is 1200000 g / mol.
[0176] Comparative Example 5
[0177] The difference between the perovskite solar cell and Example 1 is that the thickness of the first interface layer and the second interface layer is 4 nm, and the molecular weight of polyvinylidene fluoride is 30000 g / mol.
[0178] Comparative Example 6
[0179] The difference between the perovskite solar cell and Example 1 is that the thickness of the first interface layer and the second interface layer is 20 nm, and the pores in both include pores with a pore size less than 1 µm.
[0180] Its preparation method is different from that of Example 1 in that:
[0181] 1) 1 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) was fully dissolved in 1 mL of N-methylpyrrolidone; 1 mg of polycarbazole phosphate was fully mixed in 1 mL of the perovskite precursor solution, and the precursor solution was 50 mg / mL of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , and the solvent of the precursor solution was mainly N,N-dimethylformamide and dimethyl sulfoxide. The polyvinylidene fluoride solution and the precursor solution were fully mixed at a volume ratio of 3:7 to complete the preparation of the solution for the first interface layer;
[0182] 2) 3 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) was fully dissolved in 1 mL of N-methylpyrrolidone; 5 mg of PCBM was mixed in 1 mL of toluene solution; the polyvinylidene fluoride solution and the PCBM solution were fully mixed at a volume ratio of 1:9 to complete the preparation of the solution for the second interface layer.
[0183] Comparative Example 7
[0184] The difference between the perovskite solar cell and Example 1 is that the thickness of the first interface layer and the second interface layer is 2 nm, and the average pore size of both is greater than 30 µm.
[0185] Its preparation method is different from that of Example 1 in that:
[0186] 1) Dissolve 0.01 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) in 1 mL of N-methylpyrrolidone; mix 1 mg of polycarbazole phosphate thoroughly in 1 mL of the perovskite precursor solution, which is a 50 mg / mL solution of FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 , and the solvent of the precursor solution is mainly N,N-dimethylformamide and dimethyl sulfoxide. Mix the polyvinylidene fluoride solution and the precursor solution thoroughly at a volume ratio of 3:7 to complete the preparation of the solution for the first interfacial layer;
[0187] 2) Dissolve 0.03 g of polyvinylidene fluoride (molecular weight: 200000 g / mol) in 1 mL of N-methylpyrrolidone; mix 5 mg of PCBM in 1 mL of toluene solution; mix the polyvinylidene fluoride solution and the PCBM solution thoroughly at a volume ratio of 1:9 to complete the preparation of the solution for the second interfacial layer.
[0188] Comparative Example 8
[0189] The difference between the perovskite solar cell and Example 1 is that the polyvinylidene fluoride in the first interfacial layer and the second interfacial layer is replaced with polyimide with a molecular weight of 200000 g / mol.
[0190] Test Example 1
[0191] Stability test of different interfacial layer samples
[0192] ① Preparation of interfacial layer samples:
[0193] Sample FTO / NiOx: Deposit nickel oxide with a thickness of 20 nm on the FTO glass substrate;
[0194] Sample FTO / NiOx / perovskite layer: Deposit nickel oxide with a thickness of 20 nm and a perovskite layer with a thickness of 600 nm on the FTO glass substrate in sequence;
[0195] Sample FTO / NiOx / PVDF (filled with polycarbazole phosphate) / perovskite layer: Deposit nickel oxide with a thickness of 20 nm on the FTO glass substrate, and then deposit an interfacial layer with a thickness of 5 nm, which includes a polyvinylidene fluoride porous framework and FA 0.85 MA 0.1 Cs 0.05 PbI 2.7 Br 0.3 (PVSK) and polycarbazole phosphate; its pore size is 6 - 8 µm, and the polyvinylidene fluoride porous framework, FA 0.85 MA 0.1Cs 0.05 PbI 2.7 Br 0.3 、The molar ratio of polycarbazole phosphate is 10-4:10-1:10-1, and finally a perovskite layer with a deposition thickness of 600 nm is formed;
[0196] ② Use X-ray photoelectron spectroscopy to characterize the surface elements and their chemical states of the interface layer samples, and the results are shown in Table 1 and Figures 3 - 5 .
[0197] Table 1. Comparison table of XPS characterization peak areas before and after aging of different structures
[0198]
[0199] From Table 1 and Figures 3 - 5 it can be seen that by setting a first interface layer between the perovskite and the hole transport layer, the aging decomposition rate of the perovskite layer can be greatly slowed down and the thermal stability of the perovskite layer can be improved.
[0200] Test Example 2
[0201] Short-circuit current-voltage test of different perovskite cells
[0202] Use a light simulator to provide a standard sunlight (AM 1.5G, 100 mW cm-2) to irradiate the perovskite cells of each example and comparative example. At room temperature, use a Shanghai Chenhua 660E electrochemical workstation to measure their initial photoelectric conversion efficiency according to GB / T 18210-2000. Before the test, the light simulator is calibrated using a standard silicon solar cell. Subsequently, the perovskite cells are aged in a 65 °C oven under nitrogen protection, and the photoelectric conversion efficiency at different aging times is recorded. The results are shown in Table 2.
[0203] Table 2. Cell aging efficiency
[0204]
[0205] As can be seen from Table 2, compared with the comparative examples, the perovskite battery in the example has a higher initial conversion efficiency and better temperature resistance. Among them, in Comparative Example 4, due to the too high molecular weight of polyvinylidene fluoride, it is difficult to disperse during its preparation, resulting in poor uniformity of the first interface layer and the second interface layer, thus affecting the initial photoelectric conversion efficiency and thermal stability of the perovskite battery, and finally leading to the complete failure of the perovskite battery after aging at 65 °C for 672 h. In Comparative Example 5, due to the too low molecular weight of polyvinylidene fluoride, the strong hydrogen bonds formed between polyvinylidene fluoride and the organic cations in the perovskite layer and the charge transport layer are greatly reduced, which not only affects the initial photoelectric conversion efficiency of the perovskite battery, but also leads to the complete failure of the perovskite battery after aging at 65 °C for 840 h; in Comparative Example 8, since the polyvinylidene fluoride in the first interface layer and the second interface layer is replaced with polyimide, the passivation effect and stability of the first interface layer and the second interface layer decrease sharply, and finally lead to the complete failure of the perovskite battery after aging at 65 °C for 168 h
[0206] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention
Claims
1. A perovskite solar cell, comprising a hole transport layer, a perovskite layer, and an electron transport layer stacked in sequence; characterized in that, A first interface layer is provided between the perovskite layer and the hole transport layer, and / or a second interface layer is provided between the perovskite layer and the electron transport layer; wherein, the first interface layer and the second interface layer include: a polyvinylidene fluoride porous framework and an interface material filled in the polyvinylidene fluoride porous framework, and the molecular weight of the polyvinylidene fluoride porous framework is 50,000 g / mol - 1,000,000 g / mol.
2. The perovskite solar cell according to claim 1, wherein The first interface layer and the second interface layer each independently include a number of pores with a pore size of N, and N satisfies: 1 µm ≤ N ≤ 30 µm.
3. The perovskite cell according to claim 2, characterized in that, The first interface layer includes a number of pores with a pore size of 3 - 15 µm; and / or, the second interface layer includes a number of pores with a pore size of 3 - 15 µm.
4. The perovskite cell according to any one of claims 1-3, characterized in that, The molecular weight of the polyvinylidene fluoride porous framework is 200,000 g / mol - 500,000 g / mol.
5. The perovskite cell according to any one of claims 1-4, characterized in that, The hole transport layer includes a hole transport material, the electron transport layer includes an electron transport material, and the interface material of the first interface layer includes a hole transport material and / or a perovskite material; and / or, the interface material of the second interface layer includes an electron transport material and / or a perovskite material.
6. The perovskite cell according to claim 5, wherein, The perovskite material in the first interface layer is the same as the material of the perovskite layer, and / or, the perovskite material in the second interface layer is the same as the material of the perovskite layer.
7. The perovskite cell according to claim 6, wherein, The interfacial material of the first interfacial layer includes a hole transport material and a perovskite material, and the molar ratio of the polyvinylidene fluoride porous framework, the perovskite material, and the hole transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1):(1×10 -2 -1); And / or, the interfacial material of the second interfacial layer includes an electron transport material and a perovskite material, and the molar ratio of the polyvinylidene fluoride porous framework, the perovskite material, and the electron transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1):(1×10 -2 -1).
8. The perovskite cell according to claim 6, characterized in that, The interfacial material of the first interfacial layer includes a hole transport material, and the molar ratio of the polyvinylidene fluoride porous framework to the hole transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1); And / or, the interfacial material of the second interfacial layer includes an electron transport material, and the molar ratio of the polyvinylidene fluoride porous framework to the electron transport material is (1×10 -5 -1×10 -3 ):(1×10 -2 -1).
9. The perovskite battery according to claim 6 or 7, characterized in that, The hole transport material is one or more of amine halide, formamidinium hydrogen halide, methylammonium hydrogen halide, inorganic metal halide, octylamine halide, phenethylamine halide, polycarbazole phosphate, [6,6]-phenyl-C61-butyric acid methyl ester, inorganic metal oxide; and / or, the electron transport material is one or more of titanium nitride, tin oxide, titanium oxide, nickel oxide, fullerene, fullerene derivative.
10. The perovskite cell according to any one of claims 1-9, characterized in that, The perovskite solar cell further includes a transparent conductive substrate, and the transparent conductive substrate is located on the surface of the hole transport layer away from the perovskite layer.
11. The perovskite cell according to claim 10, wherein, The perovskite solar cell includes: a transparent conductive substrate, a hole transport layer, the first interface layer, a perovskite layer, the second interface layer, an electron transport layer, and an electrode stacked in sequence.
12. The perovskite cell according to claim 11, wherein A hole blocking layer is provided on the surface of the electron transport layer.
13. The perovskite cell according to any one of claims 1-12, characterized in that, The thickness of the first interface layer is 0.1 - 50 nm; and / or, the thickness of the second interface layer is 0.1 - 50 nm.
14. The perovskite cell according to claim 13, characterized in that, The thickness of the first interface layer is 1 - 15 nm; and / or, the thickness of the second interface layer is 1 - 15 nm.
15. A method for preparing a perovskite solar cell according to any one of claims 1-14, characterized in that, Including the following steps: Disperse the first interface material in a solvent, add polyvinylidene fluoride, and make the concentration of polyvinylidene fluoride 1 - 200 mg / mL, and the concentration of the first interface material 0.1 - 200 mg / mL. After mixing, a first slurry is obtained, and the first slurry is coated on the surface of the hole transport layer to obtain the first interface layer; Coat a perovskite precursor solution on the surface of the first interface layer, and anneal to obtain the perovskite layer; The second interfacial material is dispersed in a solvent, polyvinylidene fluoride is added, and the concentration of polyvinylidene fluoride is 1 - 200 mg / mL, and the concentration of the second interfacial material is 0.1 - 200 mg / mL. After mixing, a second slurry is obtained, and the second slurry is coated on the surface of the perovskite layer to obtain a second interfacial layer; An electron transport layer is fabricated on the surface of the second interfacial layer.
16. The preparation method according to claim 15, characterized in that, In the first slurry, the concentration of polyvinylidene fluoride is 10 - 50 mg / mL, and the concentration of the first interfacial material is 0.3 - 100 mg / mL; And / or, in the second slurry, the concentration of polyvinylidene fluoride is 0.5 - 5 mg / mL, and the concentration of the second interfacial material is 0.3 - 100 mg / mL.
17. A stacked battery, characterized in that, Comprising the perovskite cell according to any one of claims 1 - 14.
18. A photovoltaic module, characterized in that, The photovoltaic module cell comprises the perovskite cell according to any one of claims 1 - 14 or the tandem cell according to claim 17.